The Influence of Emotional Intelligence Towards Investing Decision - Siloam, Yosafat Chrisologus; Gunawan, Lenny (Universitas Ciputra Surabaya, 2023)
This study has a goal to analyze the influence of emotional intelligence towards investing decisions. Emotional intelligence covers 5 major part namely motivation, self-awareness, handling feelings, social aptitude, and empathy. This study only focuses on 3 major parts based on pre-survey namely motivation, self-awareness, and handling feelings. This study uses a purposive quantitative method conducted to 97 investors that reside in Indonesia and analyzed using multiple regression. The finding of this research is there are simultaneous effects of emotional intelligence towards investing decisions. This research also find that motivation and self-awareness has not significant effect individually towards investing decision,